MEASURING EXPERIENCE IN INTERNATIONAL BUSINESS: A SYSTEMATIC LITERATURE REVIEW - PARRACHO, João; SILVA, Susana (Studia Universitatis Babeș-Bolyai Oeconomica, 2021)
The paper explores the indicators that measure the experience in international business. Literature review was used to ascertain the state of the art of the existing indexes and theories. The internationalisation of businesses is a fundamental strategic step to increase companies' competitive advantage and profits. Nevertheless, even though internationalisation is widely accepted as an important source of value for companies and is a broad object of investigation, there is still much to study about how to measure experience at the level of international business. The absence of a coherent approach to measure experience in international businesses in past empirical studies made it difficult to create a solution with theoretical concepts that would support further studies in this matter. The results are not contradictory, but complementary, as, through individual internationalization indicators, it is possible to evolve and create indices, such as the Transnationality Index or the Transnational Activities Spread Index. The biggest constraint on the analysed indices is the fact that they focus mainly on the internationalisation of transnational companies and the type of data that was used to build the indexes (secondary data). However, by studying international experience through the number of years and the network spread, it is possible to overcome some of the existing challenges. JEL classification: M16; F23; F20.